A Research On Financial Expenditure And Green Economic Growth: Evidence From Highly Polluting Asian Economics (Journal of Namibian Studies : History Politics Culture, 2023)
In modern times, the economic development speed of Asian countries is not as fast as the average speed of European and American countries, and the economies of Asian countries have gradually normalized. Purpose: Asian countries need to improve the speed of economic growth and economic benefits, and can only conduct market analysis through government departments and control the structure and model of financial expenditure, but such economic growth is at the expense of polluting the environment. To gather evidence for highly polluting Asian economies, it is necessary to analyze financial expenditure models in Asian countries and the impact of financial expenditure on green economic growth. Methodology: In this paper, the Cobb Douglas model was used to analyze the financial expenditure in Asia in detail, and the impact of the relevant policies of financial expenditure in Asia on the growth of Asia's green economy has been analyzed. Research findings: The environmental pollution index in Asia is generally high, and the financial expenditure on environmental protection can increase the growth rate of the green economy by 18.6%. Science and education expenditure, social security expenditure and employment expenditure can also increase the growth rate of the green economy to a certain extent and effectively reduce environmental pollution. Research implications: Financial expenditure in Asia severely constrains green economic growth, and the development of Asian economies has created highly polluting Asian economies. Practical implications: The structure of financial expenditure in Asia needs to be adjusted to increase the share of the green economy and adhere to sustainable environmental development.